InfoNice: Easy Creation of Information Graphics - Wang, Yun; Zhang, Haidong; Huang, Ray; Chen, Xi; Yin, Qiufeng; Hou, Zhitao; Zhang, Dongmei; Luo, Qiong; Qu, Huamin (ACM CHI Conference on Human Factors in Computing Systems, 2018)
Information graphics are widely used to convey messages and present insights in data effectively. However, creating expressive data-driven infographics remains a great challenge for general users without design expertise. We present InfoNice, a visualization design tool that enables users to easily create data-driven infographics. InfoNice allows users to convert unembellished charts into infographics with multiple visual elements through mark customization. We implement InfoNice into Microsoft Power BI to demonstrate the integration of InfoNice into data analysis workflow seamlessly, bridging the gap between data exploration and presentation. We evaluate the usability and usefulness of InfoNice through example infographics, an in-lab user study, and real-world user feedback.